The Influence of Career Adaptability and Job Crafting on Performance Mediated by Job Satisfaction among Telkomsel Bengkulu Employees (The Manager Review, 2024)
This study aims to identify factors affecting job satisfaction and employee performance amidst organizational structural changes, such as the shift to outsourcing. Career adaptability and job crafting are the primary focuses, as employees who feel disengaged or lack opportunities for self-development tend to experience decreased motivation and performance. The research employs a quantitative causality method. Data was collected using a closed-ended questionnaire from a sample of 395 individual employees at Telkomsel Bengkulu. The data was analyzed using the SEM (Structural Equation Modeling) model via PLS 3.9 software. Data collection involved an online survey distributed through Google Forms, offering advantages such as ease of distribution, wide reach, convenience, quick delivery, and direct respondent access via their devices. Researchers distributed online questionnaires via WhatsApp social media and email. The study reveals that career adaptability positively and significantly impacts employee job satisfaction, meaning that better career adaptation leads to higher job satisfaction. Additionally, job crafting positively and significantly affects job satisfaction, indicating that employees' efforts to tailor their jobs enhance their satisfaction. Job satisfaction significantly influences employee performance, suggesting that higher job satisfaction contributes to improved performance. Career adaptability also positively affects performance, showing that good career adaptation can enhance employee performance. Although the impact of job crafting on performance is weaker, it still indicates a positive relationship. Job satisfaction serves as a crucial mediator in the relationship between career adaptability and employee performance, as well as between job crafting and performance. This highlights the key role of job satisfaction in linking career adaptability and job crafting with improved employee performance.